Creating the self in the contemporary American theatre - Andreach, Robert J. (Southern Illinois University Press, 1998)
Exploring the theatre from the 1960s to the present, Robert J. Andreach shows the various ways in which the contemporary American theatre creates a personal, theatrical, and national self. Andreach argues that the contemporary American theatre creates multiple selves that reflect and give voice to the many communities within our multicultural society. These selves are fragmented and enclaved, however, which makes necessary a counter movement that seeks, through interaction among the various parts, to heal the divisions within, between, and among them.